2020
DOI: 10.21608/ejchem.2020.43238.2883
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and In vitro Antimicrobial Activity of Florfenicol-Chitosan Nanocomposite

Abstract: In this paper, rapid, easy and cheap sonochemical method was described for synthesis of florfenicol-chitosan nanocomposite and to evaluate its anti-bacterial effect against Escherichia coli (ATCC35218), Salmonella typhymurium (ATCC14028) and Staph. aureus (ATCC29213). Florfenicol-chitosan nanocomposite was fully characterized for index, identification and morphology properties. Results of zeta potential for florfenicol-chitosan nanocomposite was -28 mV. Brunner-Emmett-Teller theory (BET) surface area was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The result of FTIR of P. clarkii chitosan revealed different functional groups of organic compounds such as out-of-plane bending (564 cm −1 ), C—O—C stretching (711 cm −1 ), and CH2 stretching (1174 cm −1 ) in chitosan. The most characteristic Raman shift peaks of the P. clarkii chitosan sheet are located between 2750 and 2930 cm −1 and related to (C-H), (CH2), and (CH3), confirming its identity in accordance with ( Varma and Vasudevan, 2020 , Youssef et al, 2021 ). On the other hand, Fernández-Pan et al (2010) reported two commercial chitosan samples from cold-water shrimp shells having high degrees of deacetylation (96 and 100%).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The result of FTIR of P. clarkii chitosan revealed different functional groups of organic compounds such as out-of-plane bending (564 cm −1 ), C—O—C stretching (711 cm −1 ), and CH2 stretching (1174 cm −1 ) in chitosan. The most characteristic Raman shift peaks of the P. clarkii chitosan sheet are located between 2750 and 2930 cm −1 and related to (C-H), (CH2), and (CH3), confirming its identity in accordance with ( Varma and Vasudevan, 2020 , Youssef et al, 2021 ). On the other hand, Fernández-Pan et al (2010) reported two commercial chitosan samples from cold-water shrimp shells having high degrees of deacetylation (96 and 100%).…”
Section: Discussionmentioning
confidence: 64%
“…The 532 nm He-Cd edge laser line with grating 1800 (450–850 nm). ND filter 3.2% was used to avoid sample burning employing 10 sec acquisition time, 5 accumulations without delay time, and spike filter ( Youssef et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nanoparticles have physicochemical characteristics superior to bulk materials due to their enormous surface to volume proportion, higher reactivity, stability, bioactivity, bioavailability, controlled particle size, controlled release of loaded drugs, and site-specific targeting. 5 8 …”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the involvement of the υ(C═N) in coordination to the Ln(III) ions. [22,23,26,[29][30][31] The bands appeared at 1622-1652 cm À1 were attributed to the carbonyl v(C═O) group. In the spectra of all the complexes, the group of carbonyl v(C═O) was significantly moved to a lower frequency due to hydrogen bond formation with OH b group.…”
Section: Infrared Spectramentioning
confidence: 99%
“…In continuation to our previous work, [ 22,23 ] the complexity behavior of several ligand substitutions with lanthanum(III) metal ions (La(III), Er(III), and Yb(III)) was investigated, and the resulting complexes were characterized with different analytical methods as well as physicochemical methods. In addition, certain complexes also undergo optoelectronic properties including an estimate of their optical band distance and energy for the highest occupied (HOMO) and the lowest unoccupied (LUMO) molecular orbitals to explore its potential for use with optoelectronic devices.…”
Section: Introductionmentioning
confidence: 96%